Energetic Ordering of Hydrogen Bond Strengths in Methanol‐Water Clusters: Insights via Molecular Tailoring Approach. Issue 10 (5th April 2022) - Patkar, Deepak; Ahirwar, Mini Bharati; Deshmukh, Milind M.
Abstract: In this work, we examine the strength of various types of individual hydrogen bond (HB) in mixed methanol‐water Mn Wm, (n+m=2 to 7) clusters, with an aim to understand the relative order of their strength, using our recently proposed molecular tailoring‐based approach (MTA). Among all the types of HB, it is observed that the OM −H…OW HBs are the strongest (6.9 to 12.4 kcal mol −1 ). The next ones are OM −H…OM HBs (6.5 to 11.6 kcal mol −1 ). The OW −H…OW (0.2 to 10.9 kcal mol −1 ) and OW −H…OM HBs (0.3 to 10.3 kcal mol −1 ) are the weakest ones. This energetic ordering of HBs is seen to be different from the respective HB energies in the dimer i. e., OM −H…OM (5.0 to 6.0 kcal mol −1 )>OW −H…OM (1.5 to 6.0 kcal mol −1 )>OM −H…OW (3.8 to 5.6 kcal mol −1 )>OW −H…OW (1.2 to 5.0 kcal mol −1 ). The plausible reason for the difference in the HB energy ordering may be attributed to the increase or decrease in HB strengths due to the formation of cooperative or anti‐cooperative HB networks. For instance, the cooperativity contribution towards the different types of HB follows: OM −H…OW (2.4 to 8.6 kcal mol −1 )>OM −H…OM (1.3 to 6.3 kcal mol −1 )>OW −H…OW (−1.0 to 6.5 kcal mol −1 )>OW −H…OM (−1.2 to 5.3 kcal mol −1 ). This ordering of cooperativity contribution is similar to the HB energy ordering obtained by the MTA‐based method. It is emphasized here that, the interplay between the cooperative and anti‐cooperative contributions are indispensable for the correct energetic ordering of these HBs. Abstract : The molecular tailoring‐based approach reveals the correct energetic ordering in various types of hydrogen bond strengths in methanol‐water clusters.